Effects of corporate entrepreneurship dimensions on organizational performance: Case of small and medium enterprises in Holeta Town, Ethiopia - Gemechu Abdissa; Abebe Ayalew; Csaba Bálint Illés; Anna Dunay (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Small and medium enterprises are paying the lion's share in the innovation-based economy of today's competitive business environment. To this effect, this study observed the effects of corporate entrepreneurship (CE) dimensions on the performance of SMEs in the town of Holeta, Ethiopia. We used both descriptive and survey research designs to meet the specified target of the study. The researchers employed both primary and secondary data sources; the former were collected from 173 participants using both primary and secondary data. The result of this study indicates that all of the explanatory variables used were statistically significant and had a positive relationship with the performance of SMEs. Thus, we recommend that owners of small and medium enterprises pay special attention to practicing CE to increase their business performance, sustainability, and competitiveness. Entrepreneurs should also come up with new and attractive product and service features to take high market shares. Furthermore, forecasting potential challenges for firms and devising possible ways of solving the situation in advance can safeguard businesses from failure.
Keywords: 650; corporate entrepreneurship; innovativeness; performance; proactiveness; risk taking; small and medium enterprises